Photophysical properties and sensing mechanism of fluorescent coumarin–chalcone hybrid for biothiols: A theoretical study. (3rd February 2022) - Zhang, Ling; Chen, Mohan; Li, Zheng; Teng, Yangxin; Wang, Guirong; Xue, Yunsheng
Abstract: The photophysical properties and sensing mechanism of a novel coumarin–chalcone hybrid fluorescent probe (CCH ) for biothiols were investigated by density functional theory (DFT) and time‐dependent density functional theory (TDDFT) methods. The theoretical calculations well reproduced the experimental spectra and clarified the experimental observed fluorescence "on–off" switching. Potential energy surface (PES) results revealed that the excited‐state intramolecular proton transfer (ESIPT) process is thermodynamically and kinetically viable for CCH, with the keto form more stable than the enol form. ESIPT process and the significant changes of the orbital energies should be responsible for the red fluorescence of CCH . The results revealed that the lowest lying transition of probe CCH corresponds to electronic transition between HOMO and LUMO with charge transfer (CT) character. The addition of cysteine to CCH breaks the conjugation and the intramolecular CT. A nonclassical photoinduced electron transfer (PET) process should contribute to the fluorescence quenching of CCH‐Cys . Thermodynamic and kinetic calculations on the recognition reaction predicted a moderate Gibbs free energy barrier, which proves the possibility of the Michael addition reaction and induces the rapid response of the probe CCH for cysteine. Abstract : In this work, we theoretically studied the biothiols‐sensing mechanism and the excited‐state intramolecular proton transfer (ESIPT) process of a novel coumarin–chalcone hybrid fluorescent probe (CCH ). The theoretical calculations well reproduced the experimental spectra and clarified the experimental observed fluorescence "on–off" switching. Potential energy surface (PES) results revealed that the ESIPT process is thermodynamically and kinetically viable for CCH .